Design and applications of protein- and peptide-based fluorescent biosensors for targeted imaging and biomolecular detection - Bertolini, Marco (The University of Edinburgh, 2025)
Fluorogenic and activatable optical sensors are indispensable tools for imaging, diagnostics, and biomolecular sensing. Developing novel chemical strategies to combine these smart probes with peptides and proteins in a targeted manner represents a significant advancement in fluorescent-based imaging and sensing. In this work, we present three distinct applications of such chemical strategies. First, we engineered a dual-receptor targeting imaging platform, termed Chemo-Click, by integrating the selectivity of chemokines for their receptors with a click-activatable fluorogenic reaction. This platform enabled the discrimination of closely related leukaemia cell lines based on their differential expression of two chemokine receptors. Second, we developed a fluorogenic biosensor for detecting the immunosuppressive drug tacrolimus in patient biofluids. This was achieved by site-specifically labeling the immunophilin FKBP12, a protein that binds tacrolimus, with a fluorogenic BODIPY dye at the drug-protein binding interface. This approach resulted in the first fluorogenic biosensor specifically designed for tacrolimus detection. Finally, we developed a small library of rationally designed peptide probes targeting the angiotensin II type 2 receptor (AT2R), a marker that is expressed in macrophages involved in pro-nociceptive signalling. A lead candidate was identified and evaluated for its macrophage-targeting performance through in vitro studies in multiple cell types and in vivo experiments in mice. Together, these examples highlight the broad applicability of targeted smart optical sensors in tackling diverse biological and clinical challenges. From enabling the discrimination of closely related cell populations to detecting drugs in patients biofluids, these technologies demonstrate their adaptability across distinct contexts. By integrating chemical innovation with biological specificity, such tools open new avenues for progress in fields such as personalized medicine, therapeutic monitoring, and in vivo molecular imaging.
Keywords: fluorescence; fluorescent biosensors; fluorophores; chemokines; FKBP12; fluorescent peptides; angiotensin III